Wybrane elementy kapitału intelektualnego w świetle założeń koncepcji zasobowej - Jasińska, Agnieszka (The chosen elements of intellectual capital in the light of the foundation of the assumption of the resource-based view of a company, 2007)
The article presents the essence of Resource-based View of a company. The author explains issue of resources, skills, competences as well as points of the importance of some of the assets of a company on the global market. The author tries to proveby, that nowadays intellectual capital is becoming one of the key factors for achieving success modern company.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (5); 2007; nr 1187, s. 255-265